2010
DOI: 10.1002/jcu.20692
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous inferior epigastric artery pseudoaneurysm

Abstract: A case of spontaneous pseudoaneurysm of the inferior epigastric artery-diagnosed on Doppler sonography-is presented. A 19-year-old boy presented with a lump in the anterior abdominal wall. Clinically a smooth, nontender, and noncompressible mass was present above umbilicus to the right of midline. A bruit was heard over the swelling. Doppler sonography demonstrated an oval hypoechoic structure in the right rectus sheath with turbulent flow. The pseudoaneurysm could be traced to the inferior epigastric artery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…From its origin, it courses upward and medially to enter the rectus sheath. Within the rectus sheath, it lies just at anterior to posterior wall of the sheath [1]. Pseudoaneurysm of the IEA is a recognised but very rare clinical entity with just a few cases reported in the literature as complication of surgery, trauma, and arterial puncture [2–4].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From its origin, it courses upward and medially to enter the rectus sheath. Within the rectus sheath, it lies just at anterior to posterior wall of the sheath [1]. Pseudoaneurysm of the IEA is a recognised but very rare clinical entity with just a few cases reported in the literature as complication of surgery, trauma, and arterial puncture [2–4].…”
Section: Discussionmentioning
confidence: 99%
“…Lam et al suggested that percutaneous transcatheter techniques may be preferable in patients with portal hypertension caused by chronic liver disease, who often have a coagulopathy and increased venous collateral in their abdominal wall [8]. Embolization with metallic coils or microcoils is successful, but it depends on the anatomy, the size of the arterial lesion, and the technical ability to place selectivity or superselectivity catheters or microcatheters [1]; also NBCA has been successfully used to treat IEA pseudoaneurysm [24]. US-guided probe compression may be useful for initial management of the pseudoaneurysms, but it may not be adequate if the pseudoaneurysm is deep seated either secondary to a large haematoma or it has a wide neck [15]; pain and discomfort at the compression site, the longtime compression (30–50 min), and incomplete occlusion constitute drawbacks [3, 4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations